Field Application of ZnO and TiO2 Nanoparticles on Agricultural Plants - Martin Šebesta; Marek Kolenčík; B. Ratna Sunil; Ramakanth Illa; Jaroslav Mosnáček; Avinash P. Ingle; Martin Urík (Agronomy, 2021)
Engineered nanoparticles (ENPs) have potential application in precision farming and sustainable agriculture. Studies have shown that ENPs enhance the efficiency of the delivery of agrochemicals and thus, have the potential to positively affect the environment, thereby improving the growth and health of the crops. However, the majority of the research on the effects of ENPs on plants and in agricultural applications have been limited to controlled laboratory conditions. These conditions do not fully consider various aspects inherent to the growth of agricultural plants in fields under changing weather and climate. Some of the most investigated ENPs in the agricultural research area are ZnO nanoparticles (ZnO NPs) and TiO2 nanoparticles (TiO2 NPs). ZnO NPs have the potential to increase crop production and stress resistance, mainly by the slow release of Zn ions to crops. Unlike ZnO NPs, TiO2 NPs have less well-understood means of action, and are generally considered as plant growth promoter. This mini review presents information compiled for ZnO and TiO2 NPs, their influence on agricultural plants with emphasis on particularly effect on plant growth, nutrient distribution and pollution remediation under field conditions. It is concluded that in order to gain a broader perspective, more field studies are needed, particularly multigeneration studies, to fully understand the effects of the ENPs on agricultural plants’ growth and improvement of their health.